2022
DOI: 10.1002/advs.202200155
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Dendrite‐Free Zinc Deposition by Red Phosphorous‐Derived Artificial Protective Layer for Zinc Metal Batteries

Abstract: Rational architecture design of the artificial protective layer on the zinc (Zn) anode surface is a promising strategy to achieve uniform Zn deposition and inhibit the uncontrolled growth of Zn dendrites. Herein, a red phosphorous‐derived artificial protective layer combined with a conductive N‐doped carbon framework is designed to achieve dendrite‐free Zn deposition. The Zn–phosphorus (ZnP) solid solution alloy artificial protective layer is formed during Zn plating. Meanwhile, the dynamic evolution mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 87 publications
1
44
0
Order By: Relevance
“…S9), where the two-dimension (2D) diffusion process of zinc-ions in Zn|GF|Zn cell is long and intense, corresponding to inhomogeneous zinc nucleation [ 56 ]. In contrast, Zn|UiO-66-GF-0.6|Zn and Zn|UiO-66-GF-2.2|Zn cells enter a stable 3D diffusion process after 30 s of planar diffusion and nucleation, which indicates that zinc ions are diffused uniformly and grow, likely as the confinement effect of UiO-66 inhibits the formation of dendrites [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…S9), where the two-dimension (2D) diffusion process of zinc-ions in Zn|GF|Zn cell is long and intense, corresponding to inhomogeneous zinc nucleation [ 56 ]. In contrast, Zn|UiO-66-GF-0.6|Zn and Zn|UiO-66-GF-2.2|Zn cells enter a stable 3D diffusion process after 30 s of planar diffusion and nucleation, which indicates that zinc ions are diffused uniformly and grow, likely as the confinement effect of UiO-66 inhibits the formation of dendrites [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…[52] The reaction kinetics of the full cell were further evaluated by the galvanostatic intermittent titration technique (Figure S21, Supporting Information), and the calculated diffusion coefficient of Zn 2+ (D Zn 2+ ) values of Zn@ZnCuHCF//V 2 O 5 cell (from 6.53 × 10 -8 to 6.12 × 10 -10 ) is higher than that of Zn//V 2 O 5 cell (from 5.72 × 10 -8 to 2.32 × 10 -11 ), which indicates the faster zinc ion diffusion kinetics in the Zn@ZnCuHCF//V 2 O 5 cell, the result is consistent with the EIS (Figure S21, Supporting Information). [63,64] Therefore, the full cell with Zn@CuHCF anode delivers a higher average discharge capacity of 198.6 mA h g -1 at 0.5 A g -1 , and 104.4 mA h g -1 at 10 A g -1 , respectively (Figure 4b and Figure S22, Supporting Information). Compared with the bare Zn//V 2 O 5 cell, the Zn@CuHCF//V 2 O 5 cell exhibits excellent rate performance due to the fast Zn 2+ deposition kinetics, and the discharge capacity can recover to the initial capacity when the current density returns to 0.5 A g -1 (Figure 4c).…”
Section: Resultsmentioning
confidence: 99%
“…e) Ragone plot of Zn@CuHCF//V 2 O 5 cell compared with previously reported AZIBs. [60][61][62][63][64][65][66] f) Schematic diagram of a flexible quasi-solid-state Zn@CuHCF//V 2 O 5 battery. g) The optical images of open circuit voltage of the flexible quasi-solid-state Zn@CuHCF//V 2 O 5 battery in various bending states.…”
mentioning
confidence: 99%
“…Yu et al prepared a ZnP-NC artifact protection coating to achieve a dendrite-free zinc anode (Figure 11d) and improve the electrochemical performance of AZIBs. 63 The same diffraction peaks in the XRD pattern of Zn@ZnP-NC also indicated that zinc and RP form a solid solution alloy. The concerted action of the ZnP alloy coating and the carbon skeleton creates electrical domain intensity and uniform flux of zinc ions, thus realizing long-term stable zinc plating/stripping.…”
Section: ■ Other Binary Zinc Alloysmentioning
confidence: 73%
“…ZnLiMn: Adapted from ref , John Wiley and Sons 2022. Zn@ZnP-NC: Adapted from ref , John Wiley and Sons 2022.…”
mentioning
confidence: 99%